Transition From Sublexical to Lexico-Semantic Stimulus Processing - Junker, Frederick Benjamin; Schlaffke, Lara; Bellebaum, Christian; Ghio, Marta; Brühl, Stefanie; Axmacher, Nikolai; Schmidt-Wilcke, Tobias (Frontiers in Systems Neuroscience, 2020)
Resembling letter-by-letter translation, Morse code can be used to investigate various linguistic components by slowing down the cognitive process of language decoding. Using fMRI and Morse code, we investigated patterns of brain activation associated with decoding three-letter words or non-words and making a lexical decision. Our data suggest that early sublexical processing is associated with activation in brain regions that are involved in sound-patterns to phoneme conversion (inferior parietal lobule), phonological output buffer (inferior frontal cortex: pars opercularis) as well as phonological and semantic top-down predictions (inferior frontal cortex: pars triangularis). In addition, later lexico-semantic processing of meaningful stimuli is associated with activation of the phonological lexicon (angular gyrus) and the semantic system (default mode network). Overall, our data indicate that sublexical and lexico-semantic analyses comprise two cognitive processes that rely on neighbouring networks in the left frontal cortex and parietal lobule.